2002
DOI: 10.1291/hypres.25.109
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms of the Antiproliferative Effects of Amlodipine in Vascular Smooth Muscle Cells from Spontaneously Hypertensive Rats

Abstract: The calcium channel blocker amlodipine continues to be of interest due to its potential proven ability to hin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…On the other hand, vascular SMCs proliferation and migration are other features of atherogenesis (10). It was reported that amlodipine inhibited exaggerated proliferation of vascular SMCs from spontaneously hypertensive rats (15). It was also showed that nifedipine inhibited platelet-derived growth factorinduced vascular SMCs migration via inhibition of activation of Pyk2/Src tyrosine kinase pathways (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, vascular SMCs proliferation and migration are other features of atherogenesis (10). It was reported that amlodipine inhibited exaggerated proliferation of vascular SMCs from spontaneously hypertensive rats (15). It was also showed that nifedipine inhibited platelet-derived growth factorinduced vascular SMCs migration via inhibition of activation of Pyk2/Src tyrosine kinase pathways (16).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscle cells (SMCs) proliferation and migration are also important features for the development of atherosclerosis. Recently, it was reported that amlodipine inhibited exaggerated proliferation of vascular SMCs from spontaneously hypertensive rats (15). Nifedipine was also shown to inhibit vascular SMCs migration (16 …”
Section: Introductionmentioning
confidence: 99%
“…Incubation of monocytic THP-1 cells with amlodipine significantly inhibited their adhesion to HUVECs in the presence of flow. Recent study results have indicated that certain calcium channel blockers might possess an ability to prevent atherosclerosis in vivo, 10 -12 and several in vitro findings have shown an inhibition of smooth muscle cell proliferation 13,14 and cytokine production 15,16 by amlodipine. Moreover, a recent prospective study of amlodipine that used a randomized evaluation method clearly suggested its dramatic efficacy in reducing cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium channel blockade amlodipine has been shown to limit the progression of arteriosclerosis and atherosclerosis in animals and humans (37,38). Although the mechanisms underlying the direct protective effects of calcium channel blockades on endothelial cell injury are not fully understood, such vasoprotective effects as the amelioration of endothelial dysfunction (39,40) and decreases in the proliferation of vascular smooth muscle cells (41), oxidative stress (37,42), and inflammation (43), are at least in part independent of the blood pressure-lowering effects of these agents. The calcium channel blockade has been shown to ameliorate hypertension and improve NO production in the vasculature and kidneys.…”
Section: Introductionmentioning
confidence: 99%